PELAKSANAAN APLIKASI SIAPKE PATI DALAM PENGELOLAAN DATA KEMISKINAN EKSTREM DAN PENDISTRIBUSIAN BANTUAN SOSIAL DI KABUPATEN PATI TAHUN 2024 - Rofi Ramadani; Dewi Erowati (Journal of Politic and Government Studies, 2025)
This study examines the implementation of the SIAPKE PATI application in managing extreme poverty data and distributing social assistance in Pati Regency. A qualitative descriptive-analytical approach was employed, using interviews, observations, and documentation. The analysis is grounded in the policy design failure framework by B. Guy Peters and the concept of the fragmented state by Ronan Paddison. The findings reveal that SIAPKE PATI does not function as a primary policy instrument but merely as an administrative tool, as it is not integrated into core processes of data management and aid distribution. This reflects a policy failure due to instrument mismatch, reinforced by governance failure characterized by weak regulation, coordination, and oversight. Furthermore, these failures culminate in a fragmented state, where the state remains present but policy implementation operates in a disconnected and unintegrated manner from the digital system. The study concludes that SIAPKE PATI does not significantly contribute to the effectiveness of extreme poverty alleviation policy.